Pengembangan Media “Pegalinu” Dalam Kemampuan Literasi Digital dan Numerasi Dasar Kelas III di SD Se-Gugus Wibisono Kecamatan Jati Kabupaten Kudus - Ade Kalpika Budiningtyas; Sri Utaminingsih; Nur Fajrie (Peneliti.net, 2022)
This study aims to analyze needs, develop products in the form of game in third grade elementary school.. In addition, the development of game literacy and numeracy game in digital literacy and basic numeracy skills for third grade elementary schools in the Wibisono cluster, Jati District, Kudus Regency. This research is a research development or Research and Development (R&D) using the Borg and Gall development method. The results of this media development have been tested for effectiveness with the results of accumulated scores by 3 material validators, namely 53,52,52 out of a maximum score of 60. An average of 87% of material expert validators were obtained. The accumulation of 3 media expert validators, namely 63.70 and 71 from a maximum score of 80, obtained an average percentage of 85%. The accumulation of expert users is 15,16,17 from a maximum score of 20, an average percentage of 80% is obtained. So that all three are included in the